Nontraumatic spleen rupture as a presentation of diffuse large B-cell lymphoma. - González González, Daniel (Cirugía del Uruguay, 2020)
Few cases of nontraumatic rupture of the spleen in diffuse B-cell lymphoma have been reported. We present a case of a 73-year-old man, multiple comorbidities that hours before biopsy puncture of the liver nodule installed abdominal pain and hypovolemic shock. An emergency operation was performed. A pathological spleen was found with a ruptured nodule, bleeding and moderate hemoperitoneum. Splenectomy was performed. At 96 hours, he installed abdominal pain and shock. The liver node and hemoperitoneum rupture and bleeding, hemodynamic instability and intraoperative death were reoperated and confirmed. The pathological anatomic study diagnosed diffuse large B-cell lymphoma.